Problems and Implementation of Multidisciplinary Islamic Studies - Anum, Adelina; Saleh, Khairul; Nasor, Nasor; Murtafiah, Nurul Hidayati; Apriyanto, Sigit (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study was to find out the stakeholders' understanding of the IAI An Nur Lampung Postgraduate Doctoral Program stakeholders towards multidisciplinary Islamic studies, what the problems faced by the IAI An Nur Lampung Postgraduate Doctoral Program in implementing Multidisciplinary Islamic Studies and the design of appropriate multidisciplinary Islamic studies to be implemented in the Postgraduate Doctoral Program. IAI An Nur Lampung. This type of research is descriptive and qualitative with data sources from online media, print media, journal articles, and books. This study found that most of the stakeholders of the Postgraduate Doctoral Program of IAI An Nur Lampung have a good understanding of inter-and multidisciplinary Islamic studies; problems in the implementation of inter- and multidisciplinary Islamic studies exist in four aspects: student aspects, lecturer aspects, curriculum aspects, and carrying capacity and policy aspects. Therefore, further studies and developments are needed in various aspects to realize a multi-talented university. The transformation of STAI An Nur into IAI An Nur Lampung has changed the epistemology of science. These changes need to be translated and poured into various levels of academic practice so that the academic community at IAI An Nur Lampung can understand and implement these changes and expectations. Studies at IAI An Nur Lampung must also be oriented towards the institute's new paradigm. One of them is the Postgraduate Doctoral Program, which seeks to develop inter, multi, and transdisciplinary Islamic studies at the doctoral program level.